Bosnia and Herzegovina Systematic Country Diagnostic Update - World Bank (World Bank, Washington, DC, 2020)
The citizens of Bosnia and Herzegovina (BiH) aspire to a future of rising living standards. Every year, thousands of people emigrate seeking a better quality of life. The country cannot afford to continue losing its people, and creating the incentives for people to stay will require meeting their wish for a better quality of life for themselves and their families. This is achievable, but it requires decisive action by all stakeholders to address identified challenges. This update develops earlier findings and priorities, reviews progress, and employs new data and analyses. It is structured in four sections. Section I describes BiH’s current situation, focusing on cross-cutting, foundational themes and distinct characteristics that could shape development outcomes. Section II describes current economic trends and key outcomes. Section III considers development constraints and how they can be overcome with respect to private sector–led growth, physical capital, human capital, and natural assets and their management. Section IV offers an updated set of priorities developed in consultation with other stakeholders to chart a path for strong, lasting, inclusive growth.